Correlation between Geography of Residence, Socio-Culture and Family Structure with Early Marriage In South Bangka - Ayudita, Ayudita (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: One of four women in the world who had married before 18 years old. Bangka Belitung Islands Province was in the third highest rate of early marriage in Indonesia. This province was mostly a coastal area that had a variety of social cultures. The purpose of the study was to analyze the correlation between the geography of residence, socio-culture, and family structure with early marriage and explore these three factors. Methods: This study used a qualitative study method with 13 informants for qualitative research (5 young women and their parents, village head, Head of Religious Affairs Office, Head of Islamic Community Development Division, Ministry of Religion). Qualitative research was conducted by conducting in-depth interviews with purposive sampling and explained through transcription, coding and categorization processes. Results: Qualitative research found that the geographical factors of residence, socio-culture and family structure influence early marriage. Conclusion: The geography of residence, socio-culture and family structure influenced early marriage. Suggestion: A synergistic effort by providing reproductive health education and sexuality education to children and adolescents. Keywords: Early marriage, geography of residence, socio-cultural, family structure, South Bangka